Epistimologi sebagai Landasan Validitas Pengetahuan - Munawaroh, Habibah Munawaroh (Maliki Interdisciplinary Journal, 2026)
Epistemology is one of the main branches of philosophy that discusses the nature of knowledge, its sources, and the criteria of truth used to assess the validity of knowledge. In the development of modern science and the information era which is characterized by the rapid flow of data and truth claims, epistemology has an important role as a methodological and normative foundation for the scientific process. This paper aims to examine the concept of epistemology, explain the main sources of knowledge such as rationalism, empiricism, and pragmatism, and analyze theories of truth which include correspondence, coherence, pragmatism, and scientific consensus. Apart from that, the discussion also highlights the role of epistemology in shaping modern scientific methods, including the influence of positivism, Karl Popper’s falsificationism, and the scientific paradigm according to Thomas Kuhn. The results of the study show that epistemology not only functions as a theoretical framework in understanding knowledge, but also as a critical guide in assessing scientific truth, validity and responsibility. Thus, epistemology becomes an important foundation for the development of science that is rational, objective and relevant to social dynamics and the challenges of the times.